ENVIRONMENTAL DISCLOSURE: ENVIRONMENTAL PERFORMANCE, INSTITUTIONAL OWNERSHIP AND AUDIT COMMITTEE PART OF GOOD CORPORATE GOVERNANCE - Listya Sugiyarti; Tissa Rahmadhianti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to determine the effect of Environmental Performance, Institutional Ownership, and Audit Committee part of Good Corporate Governance on Environmental Disclosure. The Good Corporate Governance (GCG) studied is institutional ownership, and audit committees.  The population in this study is Primary Consumer Sector Companies of the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2018-2022. The total sample is 70 Financial Statement data. The sample in this study was determined by purposive sampling method. The data analysis technique used is the E-views Series 12 application. The analysis method used is Quantitative Analysis with an Associative approach. The results of this study show that environmental performance, institutional ownership and Audit Committee simultaneously affect Environmental Disclosure. Environmental Performance affects Environmental Disclosure, Institutional Ownership has no effect on Environmental Disclosure, and Audit Committee has no effect on Environmental Disclosure.